Roles of proteome dynamics and cytokinin signaling in root to hypocotyl ratio changes induced by shading roots of Arabidopsis seedlings - Novák, Jan; Černý, Martin; Pavlů, Jaroslav; Zemánková, Jana; Skalák, Jan; Plačková, Lenka; Brzobohatý, Břetislav (Plant & cell physiology, 2015)
In nature, root systems of most terrestrial plants are protected from light exposure by growing in a dark soil environment. Hence, in vitro cultivation in transparent Petri dishes leads to physiological perturbations, but the mechanisms underlying root-mediated light perception and responses have not been fully elucidated. Thus, we compared Arabidopsis thaliana seedling development in transparent and darkened Petri dishes at low light intensity (20 µmol m(-2) s(-1)), allowing us to follow (inter alia) hypocotyl elongation, which is an excellent process for studying interactions of signals involved in the regulation of growth and developmental responses. To obtain insights into molecular events underlying differences in seedling growth under these two conditions, we employed liquid chromatography-mass spectrometry (LC-MS) shotgun proteomics (available via the PRIDE deposit PXD001612). In total, we quantified the relative abundances of peptides representing 1,209 proteins detected in all sample replicates of LC-MS analyses. Comparison of MS spectra after manual validation revealed 48 differentially expressed proteins. Functional classification, analysis of available gene expression data and literature searches revealed alterations associated with root illumination (inter alia) in autotrophic CO2 fixation, C compound and carbohydrate metabolism, and nitrogen metabolism. The results also indicate a previously unreported role for cytokinin plant hormones in the escape-tropism response to root illumination. We complemented these results with reverse transcription followed by quantitative PCR (RT-qPCR), chlorophyll fluorescence and detailed cytokinin signaling analyses, detecting in the latter a significant increase in the activity of the cytokinin two-component signaling cascade in roots and implicating the cytokinin receptor AHK3 as the major mediator of root to hypocotyl signaling in responses to root illumination.
Keywords: Mass Spectrometry; Hypocotyl elongation; světlo; Arabidopsis; Cytokinins; Proteomics; Photosynthesis; Shaded root; Down-Regulation; rostlinné proteiny; Signal Transduction; kořeny rostlin; Chromatography, Liquid; down regulace; Hypocotyl; aktiny; Actins; signální transdukce; Light; Plant Proteins; chromatografie kapalinová; fotosyntéza; Cytokinin; hypokotyl; Proteome; proteom; cytokininy; Plant Roots; hmotnostní spektrometrie; Arabidopsis thaliana; proteomika